Principles for Management and Development of Sea Passenger Ports - Jugović, Alen; Perić, Ana; Kolanović, Ines (Promet - Traffic&Transportation, 2006)
The management of sea passenger ports has been determinedby sequences of circumstances closely connected withthe complex function of any port; together with its reflection ontraffic and economic system. Each of those principles has certainimpact on the development, management and evaluationof a port in different stages of growth. However, all the resultsthat are gained present evaluations and ratings of each port individuallyand those results and ratings are crucial in the traveller’sdecision of which sea passenger port they should take. Allthose principles that are used for evaluation of a port are usedas well for establishing the travel routes, in fact, its departureand arrival point. The importance of those departure and arrivalpoints is dissimilar for each port and it is also possible thatin different stages of development those points can increase orreduce its importance. Very often it is likely that those principleshave positive impact and in some other stage they can have negativereflection on the port.Numerous principles for the development and managementof sea passenger ports in the Republic of Croatia are notapplied in all the stages of the port existence. The problem of seapassenger ports is frequently considered as the forgotten issuewhich is one of the vital parts of the whole national economicwith very high multiple effects and possible results. The purposeof this work is the SWOT analyses which provides a clear picturethat successful managing of the ports comes through balancedefforts and achievements of the town, region and thecountry as a whole.The purpose of this paper is to analyze all the possibilitiesand steps that have to be taken in order to determine the advantagesand the disadvantages of not just the port but rather of thetown where the port is located as well. It has to be investigatedwhat is having impact on the town, its attractions and the possibilityfor successful running of the port. Apart from thewell-known elements which are location, natural characteristicsof a port, organization of work, etc. The measures of theport politics are applied to further analyses and evaluations ofcompletely new principles such as: resources, tourist offers,structure, public sectors and town future planning, communication,image and trends.The results of the survey are applied so that management ofthe sea passenger ports should be run in a way to create a system which would continue to develop all the principles that aretightly connected to the port’s functioning and all that in orderto form a port which would be major a factor to transform notjust the town where the port is located but the whole region andmore.